Functional analyses of AmpC beta-lactamase through differential stability. - Beadle, B. M. (Cold Spring Harbor Laboratory Press, 1999)
Despite decades of intense study, the complementarity of beta-lactams for beta-lactamases and penicillin binding proteins is poorly understood. For most of these enzymes, beta-lactam binding involves rapid formation of a covalent intermediate. This makes measuring the equilibrium between bound and free beta-lactam difficult, effectively precluding measurement of the interaction energy between the ligand and the enzyme. Here, we explore the energetic complementarity of beta-lactams for the beta-lactamase AmpC through reversible denaturation of adducts of the enzyme with beta-lactams. AmpC from Escherichia coli was reversibly denatured by temperature in a two-state manner with a temperature of melting (Tm) of 54.6 degrees C and a van't Hoff enthalpy of unfolding (deltaH(VH)) of 182 kcal/mol. Solvent denaturation gave a Gibbs free energy of unfolding in the absence of denaturant (deltaG(u)H2O) of 14.0 kcal/mol. Ligand binding perturbed the stability of the enzyme. The penicillin cloxacillin stabilized AmpC by 3.2 kcal/mol (deltaTm = +5.8 degrees C); the monobactam aztreonam stabilized the enzyme by 2.7 kcal/mol (deltaTm = +4.9 degrees C). Both acylating inhibitors complement the active site. Surprisingly, the oxacephem moxalactam and the carbapenem imipenem both destabilized AmpC, by 1.8 kcal/mol (deltaTm = -3.2 degrees C) and 0.7 kcal/mol (deltaTm = -1.2 degrees C), respectively. These beta-lactams, which share nonhydrogen substituents in the 6(7)alpha position of the beta-lactam ring, make unfavorable noncovalent interactions with the enzyme. Complexes of AmpC with transition state analog inhibitors were also reversibly denatured; both benzo(b)thiophene-2-boronic acid (BZBTH2B) and p-nitrophenyl phenylphosphonate (PNPP) stabilized AmpC. Finally, a catalytically inactive mutant of AmpC, Y150F, was reversibly denatured. It was 0.7 kcal/mol (deltaTm = -1.3 degrees C) less stable than wild-type (WT) by thermal denaturation. Both the cloxacillin and the moxalactam adducts with Y150F were significantly destabilized relative to their WT counterparts, suggesting that this residue plays a role in recognizing the acylated intermediate of the beta-lactamase reaction. Reversible denaturation allows for energetic analyses of the complementarity of AmpC for beta-lactams, through ligand binding, and for itself, through residue substitution. Reversible denaturation may be a useful way to study ligand complementarity to other beta-lactam binding proteins as well.